2010
DOI: 10.1056/nejmoa0906644
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Public-Access Defibrillation in Japan

Abstract: Nationwide dissemination of public-access AEDs in Japan resulted in earlier administration of shocks by laypersons and in an increase in the 1-month rate of survival with minimal neurologic impairment after an out-of-hospital cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
417
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 531 publications
(433 citation statements)
references
References 24 publications
10
417
0
6
Order By: Relevance
“…The number of public‐access AEDs has rapidly increased, with >360 000 devices located throughout Japan in 2012 (including 25 000 in Osaka Prefecture) 9. Previous studies suggested that the nationwide dissemination of public‐access AEDs allowed early defibrillation by bystanders, leading to increased survival rates after OHCA 10, 11. Nevertheless, in the era of the public‐access defibrillation (PAD), we identified no published studies of the long‐term effects of bystander CPR and public‐access AED on the outcome of exercise‐related OHCA.…”
Section: Introductionmentioning
confidence: 92%
“…The number of public‐access AEDs has rapidly increased, with >360 000 devices located throughout Japan in 2012 (including 25 000 in Osaka Prefecture) 9. Previous studies suggested that the nationwide dissemination of public‐access AEDs allowed early defibrillation by bystanders, leading to increased survival rates after OHCA 10, 11. Nevertheless, in the era of the public‐access defibrillation (PAD), we identified no published studies of the long‐term effects of bystander CPR and public‐access AED on the outcome of exercise‐related OHCA.…”
Section: Introductionmentioning
confidence: 92%
“…Many studies, including a prospective, randomized trial, have shown that public access defibrillation (PAD) programs improve the rate of survival among patients with an OHCA. As a result of these findings, PAD programs have been introduced in many areas 8, 10, 11, 12, 17, 18…”
Section: Introductionmentioning
confidence: 99%
“…Long‐term survival can increase as much as 2 to 3 times if a bystander/first responder also uses an automated external defibrillator (AED) before emergency medical service (EMS) arrival 2, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16. Many studies, including a prospective, randomized trial, have shown that public access defibrillation (PAD) programs improve the rate of survival among patients with an OHCA.…”
Section: Introductionmentioning
confidence: 99%
“…An automated external defibrillator (AED) allows bystander rescuers to defibrillate out‐of‐hospital ventricular fibrillation (VF) or pulseless ventricular tachycardia (VT) before the emergency medical service arrives 17, 18, 19, 20, 21, 22, 23, 24, 25. In fact, nationwide dissemination of publicly accessible AEDs in Japan resulted in an earlier administration of shocks by bystanders and has improved the rate of survival 26, 27. The AED effectiveness is dependent on the device's ability to detect lethal arrhythmias and on the operator's ability to use the device correctly,28 and errors associated with AED use have been identified as device dependent or operator dependent 29, 30.…”
Section: Introductionmentioning
confidence: 99%